Impact of Infrastructure and Entrepreneurial Ecosystems on MSME Growth in Medan: An Islamic Economics Perspective - Muhammad Ridho; Isnaini Harahap; Nurbaiti (Al-Muamalat, 2025)
This study investigates the impact of infrastructure development and the entrepreneurial environment on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Medan City, with a focus on integrating Islamic economic principles. Using a quantitative correlational design, the research examines the causal relationships between infrastructure (X1), the entrepreneurial environment (X2), and MSME growth (Y). Data were collected through a structured questionnaire from 100 MSME owners, and analyzed using multiple linear regression. Findings indicate that both infrastructure and the entrepreneurial environment significantly influence MSME growth; however, the entrepreneurial environment emerged as a more dominant factor, with a significant positive effect. Infrastructure development showed a positive but statistically insignificant impact on MSME growth. The study suggests that while physical infrastructure plays a role, a supportive and ethical entrepreneurial environment, grounded in Islamic principles such as justice, fairness, and sustainability, is crucial for fostering sustainable MSME growth. This study also emphasizes the importance of integrating Islamic economic values to create a competitive and equitable business ecosystem in Medan, aligning with the objectives of maqāṣid al-sharīʿah.